MENGUAK EKSISTENSI RENTENIR (STUDI RELATIONSHIP LENDING DI PASAR KUTOARJO) - Ardi Surya Satria Ridwan; Apriani Dorkas Rambu Atahau (BBM (Buletin Bisnis & Manajemen), 2016)
The purpose of this study is to describe of relationship lending between moneylenders and small traders in the Pasar Kutoarjo by the scope of the relationship, the distance from the borrower, the frequency of contact and the exclusivity of lenders. This study uses primary data from moneylenders and small traders in Pasar Kutoarjo and analysed qualitatively. The results show that relationship lending in terms of the scope of the relationship, the distance from the borrower, the frequency of contact and the exclusivity of lenders between moneylenders and small traders in the Pasar Kutoarjo developed well. It supports the characteristics of microfinance institution as stated by  financial service authority (OJK)  pursuant Act number 1/2013 in terms of simple, quick and non written general procedures and loan agreement.  Keywords: money lenders, relationship lending, informal financial institution, analysis